MALADMINISTRATION EDUCATION CONCEPT TO STRENGTHEN GOOD GOVERNANCE - Maulidhyna, Nessa (Universitas 17 Agustus 1945 Surabaya, 2025)
In the era of globalization, maladministration poses a significant challenge to the implementation of good governance, undermining public trust and causing economic and social losses. This study aims to develop an effective maladministration education model to strengthen good governance practices. Using a literature review method, the research analyzes relevant literature on maladministration and good governance, including policies, journal articles, and research reports. The findings indicate that maladministration education can enhance awareness and understanding among citizens and government officials regarding the negative impacts of maladministration and the importance of transparency, accountability, and integrity. Education through formal curricula, interactive training, and public campaigns has been shown to reduce maladministration rates by 30% over the past two years. This study suggests integrating maladministration education into formal and non-formal education systems to reach broader segments of society while encouraging active public participation in administrative oversight. The research underscores the importance of collaboration among governments, educational institutions, and communities in creating a more equitable and accountable governance environment.